2017
DOI: 10.1590/1809-4430-eng.agric.v37n5p940-952/2017
|View full text |Cite
|
Sign up to set email alerts
|

Alterations on the Evapotranspiration of Sugarcane Cultivars Under Distinct Salinity Levels Applied in the Fertigation

Abstract: ABSTRACT:The aim of this research was to evaluate the effect of distinct levels of salinity on the evapotranspiration of the RB867515, RB855453, RB92579 and RB928064 sugarcane cultivars. The evapotranspiration was monitored during daytime period under meteorological conditions influenced, mainly by cloud variations. The salinity values were established by addition of 0, 50, 100 and 150 mM of Sodium Chloride (NaCl) to the nutrient solution, which was applied by fertigation, in such way that the electrical condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In studies with sugarcane under salinity, Simões et al (2016) obtained a reduction of 8% in the CD due to the use of saline water (8 dS m -1 ), while Toledo et al (2017) observed a decreasing linear effect on sugarcane evapotranspiration due to the higher NaCl concentration in the water used for irrigation. where: θ FC -volumetric water content at field capacity, m 3 m -3 ; θ PWP -volumetric water content at permanent wilting point, m 3 m -3 ;…”
Section: Resultsmentioning
confidence: 99%
“…In studies with sugarcane under salinity, Simões et al (2016) obtained a reduction of 8% in the CD due to the use of saline water (8 dS m -1 ), while Toledo et al (2017) observed a decreasing linear effect on sugarcane evapotranspiration due to the higher NaCl concentration in the water used for irrigation. where: θ FC -volumetric water content at field capacity, m 3 m -3 ; θ PWP -volumetric water content at permanent wilting point, m 3 m -3 ;…”
Section: Resultsmentioning
confidence: 99%